Deterrence and reciprocity effects on tax compliance: experimental evidence from Venezuela - Ortega, Daniel (2013)
Why do people pay taxes? One obvious answer is that there are enforcement mechanism (fines and penalties) established by the State. This deterrence approach to tax compliance has been formally analyzed in the seminal paper by Allingham and Sandmo (1972). In this model tax payers decide whether and how much to evade taxes in the same way they would approach any risky decision or gamble, that is, by maximizing expected utility (Slemrod (2007)). Under this framework tax evasion is negatively associated with the probability of detection and the severity of punishment. (Párrafo extraído del texto a modo de resumen)